Integrated agro-industrial parks in Ethiopia: Status, success and challenges with a focus on Yirgalem IAIP - Alemnew, Teklebirhan; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2025)
This study aims to assess the current state, successes, and challenges of Integrated Agro-Industrial Parks (IAIPs) in Ethiopia, with a specific focus on the Yirgalem Integrated Agro-Industrial Park (YIAIP). The analysis is based on an extensive literature review and semi-structured interviews with key informants (KIIs). By examining the current state of Ethiopia's IAIPs, the research provides valuable insights into their successes and shortcomings, offering critical lessons to enhance the sustainability of IAIPs in Ethiopia and guide the development of similar initiatives in other Sub-Saharan African countries.